Correlation between EFL Students’ Language Aptitude and their English Proficiency - Kartini Tobroni; Farah Natchiar Mohd Khaja (Journal of English Education and Teaching, 2021)
This study is designed to investigate the correlation between EFL students’ language aptitude and their English proficiency. The data were collected from sixty-five students in the end of their eighth semester at the English department in faculty of teacher training in UIN Raden Fatah Palembang.The students took a foreign language aptitude test(both explicit and implicit LLAMA tests) and an English proficiency test (TOEFL). The collected data was analyzed using Pearson-Product Moment correlation test. It reveals that Pearson correlation between LLAMA explicit scores and TOEFL scores is significant at 0.676, P < 0.01 (2-tailed), so the correlation between LLAMA explicit scores and TOEFL scores is considered moderate. In addition, the correlation between LLAMA implicit scores and TOEFL scores is significant at 0.422, P < 0.01 (2-tailed), therefore, the correlation between LLAMA implicit scores and TOEFL scores is considered low.